If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.2 + 0.8 = m + -1 Combine like terms: -1.2 + 0.8 = -0.4 -0.4 = m + -1 Reorder the terms: -0.4 = -1 + m Solving -0.4 = -1 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -0.4 + -1m = -1 + m + -1m Combine like terms: m + -1m = 0 -0.4 + -1m = -1 + 0 -0.4 + -1m = -1 Add '0.4' to each side of the equation. -0.4 + 0.4 + -1m = -1 + 0.4 Combine like terms: -0.4 + 0.4 = 0.0 0.0 + -1m = -1 + 0.4 -1m = -1 + 0.4 Combine like terms: -1 + 0.4 = -0.6 -1m = -0.6 Divide each side by '-1'. m = 0.6 Simplifying m = 0.6
| 7x^2-7x^2*4= | | x-2+56=0 | | 8n+2=5n+11 | | 12=34-x | | x^3+2x^2+5x-26=0 | | 6(y-2)= | | 6x*4x*2x= | | 8r^3-4r^2+14r-7= | | 8-3y=-19 | | 14+7w= | | 3(4x-.5)=5(3x+1) | | 6x(4x+3)-(5-4x)+7x^2*(1-4)= | | c=3.14(d) | | c=7x^2+5x-5 | | x-15+5=10 | | 10x-52=83+x | | -1=4/3(-4)+6 | | 18-5(2x+3y)= | | 10=.5(7)-9 | | 5x^2+6x-560=0 | | 2=3(-9)-12 | | V=F(R^2-D^2) | | -6(1)+7=-1 | | 119=x+2x+(x+19) | | 14-p=17 | | 17-14p= | | 0+3(-10)=16 | | x+3y+(2x-3y-9)i=0 | | 6x-6=6x+18 | | 2(5)=4(-2)-6 | | 64x^4-49= | | y-(-1)=-3/5(5)-3 |